2022
DOI: 10.7759/cureus.23657
|View full text |Cite
|
Sign up to set email alerts
|

Flipped Classroom versus Traditional Didactic Classroom in Medical Teaching: A Comparative Study

Abstract: Background The effective and efficient delivery of healthcare services that the National Medical Commission (NMC), India desires from Indian Medical Graduate (IMG) can only be fulfilled if the learner’s participation is extensive. Flipped classroom (FC) may promote enhanced as well as meaningful learning and critical thinking in students. By implementing this method trend can be changed from a teacher-centered approach to a student-centered approach, thus teaching-learning becomes more effective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…Some benefits include increased flexibility and personalization of study schedules [32,33]. One randomized controlled study showed that a virtual learning environment significantly improved medical student satisfaction/engagement and recall compared with traditional didactic teaching [34], which constitutes passive learning [35]. The flipped classroom strategy, whereby students review instructional content online on their own time and then come together for class time dedicated to student-centered learning activities [36], has been shown to significantly improve student performance and satisfaction in a preclinical medical education setting [37].…”
Section: Discussionmentioning
confidence: 99%
“…Some benefits include increased flexibility and personalization of study schedules [32,33]. One randomized controlled study showed that a virtual learning environment significantly improved medical student satisfaction/engagement and recall compared with traditional didactic teaching [34], which constitutes passive learning [35]. The flipped classroom strategy, whereby students review instructional content online on their own time and then come together for class time dedicated to student-centered learning activities [36], has been shown to significantly improve student performance and satisfaction in a preclinical medical education setting [37].…”
Section: Discussionmentioning
confidence: 99%
“…The education in the Health Sciences has experienced enormous changes in the last few years, which have led to the implementation of diverse models focused on the student, such as the case of the Flipped Classroom (19,56) . In addition, the COVID-19 pandemic, which started in 2020, has been perceived by the educational community as a challenge for the current learning methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the development of skills associated with Flipped Classroom, it is observed that the acquisition of both technical skills required in their respective disciplines (25,51) as well as other general ones such as critical thinking (47) , whose importance in health related professions has been recognized in the literature (56,66) .…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Researchers found that perception of students toward medical teaching could be greatly improved in flipped classroom. It helped students achieve better academic performance in their learning [21,22]. Recently, a study also indicated that flipped classroom teaching increased students' learning effectiveness in physiology course, and facilitated the learning of the follow-up medical courses in long-term [2].…”
Section: Flipped Classroom Can Improve Students' Learning Outcomesmentioning
confidence: 99%